Salt Wasting Syndrome: Serial Cases - Anggelia, Vivi; Nugroho, Agung Adi; Ayu, Nyoman Paramita; Adnyana, I Wayan Losen (Green Publisher Indonesia, 2024)
Hyponatremia is one of the electrolyte disturbances that can be found in patients with central nervous system disorders, the most cases of hyponatremia are the Syndrome of Inappropriate Antidiuretic Hormone/SIADH compared to hyponatremia in Cerebral Salt Wasting Syndrome/CSWS and it is not uncommon to also occur in patients undergoing chemotherapy treatment without accompanying head abnormalities are referred to as Renal Salt Wasting Syndrome (RSWS). There is difficulty differentiating these two conditions due to almost the same clinical symptoms. Evaluation of volume status and monitoring of urate excretion fraction can help differentiate SIADH from RSWS and CSWS. Management requiring prompt diagnosis is essential to prevent severe hyponatremia from substantially causing cerebral edema and thereby reducing the risk of seizures. Fluid resuscitation therapy and sodium restoration are important. This case series report injured 2 CSWS patients after head trauma with different treatments and hyponatremia due to cisplatin induced RSWS.